Factores de riesgo de infección por cepas de Escherichia coli shigatoxigénicas en gatos y perros. - Bentancor, A. (2008)
Hemolytic Uremic Syndrome caused by Shiga toxin-producing Escherichia coli, STEC, is endemic in Argentina. Although the disease is classified as a Food Transmitted Disease, person-toperson infection has been postulated to have a high impact in our country. Given the close relationship between pets and their owners, the pet-owner transmission route has been analyzed in urban centers. The aim of this work is to communicate the risk-factor analysis in pets that carry STEC in Buenos Aires, Argentina, providing useful information to evaluate the risk of transmission of this pathogen. Rectal swabs were collected from 149 cats and 450 dogs from April 2005 to March 2006. A questionnaire was filled in for each animal. Bacteria from samples were cultured and screened for Shiga-toxin genes (stx) by PCR. STEC isolated were recovered from stx-positive samples, in this study, all isolated strains were stx2+. Of the 113 healthy cats sampled, 4 (2.7%) were stx+. Of the 373 healthy dogs, 4 (1.1%) were stx+, while 1 of 29 (3.4%) dogs with diarrhea was infected. Statistical analyses of 12 parameters revealed several risk-factors for the presence of STEC: potentially contaminated food, age of the pets, frequent pet-to-pet contact and season. No significant differences between healthy or diarrheic pets concerning risks for carrying STEC were observed.